2017
DOI: 10.1159/000487483
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of the Hepatic Vagus Nerve against Liver Metastasis in Mice

Abstract: Objective(s): Although accumulating evidence has shown that the autonomic nervous system is involved in liver pathology, its role in regulating cancer development remains unclear. The purpose of this study was to elucidate its detailed mechanisms. Methods: A mouse model of liver metastasis of colorectal cancer was used. To elucidate the potential mechanisms involved, we examined the effect of selective hepatic vagotomy on the survival rate and liver-to-body weight. We further evaluated the possible involvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In melanoma, NK-cell activity is determined by genetic immune predisposition protecting from liver metastasis (8). In addition, hepatic stellate cells (9), but also innervation determine metastatic susceptibility of the hepatic niche (10). Last, but not least, hepatocytes (HC) should not be neglected as active members of the hepatic niche.…”
Section: Introductionmentioning
confidence: 99%
“…In melanoma, NK-cell activity is determined by genetic immune predisposition protecting from liver metastasis (8). In addition, hepatic stellate cells (9), but also innervation determine metastatic susceptibility of the hepatic niche (10). Last, but not least, hepatocytes (HC) should not be neglected as active members of the hepatic niche.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier animal studies in the last century demonstrated that vagotomy promotes the development of gastrointestinal cancers such as gastric 31 , colon 32 and pancreatic 33 cancers. Recent research also indicates that partial vagotomy increases metastasis in breast and colon cancers 35 , 36 . Partecke et al reported that subdiaphragmatic vagotomy exacerbates pancreatic cancer progression involving tumor-associated macrophages (TAM) producing tumor necrosis factor-alpha (TNF-α) in a murine model 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, autonomic denervation clinical studies for the treatment of hypertension have failed ( Bhatt et al, 2014 ). Hepatic vagotomy may also cause negative changes in feeding behavior, increased hypoglycemic episodes, may affect liver regeneration and cause increased metastasis during liver cancer ( Kiba, 2002 ; Donovan and Watts, 2014 ; Hiramoto et al, 2017 ). In our rat studies, ligation of the hepatic branch did not increase glycemic control following the IVGTT ( Figure 6A ).…”
Section: Discussionmentioning
confidence: 99%
“…Ligation of neuronal fibers innervating the liver has been shown to affect plasma glucose (PG) possibly though disinhibition of vagal efferents innervating the pancreas ( Lee and Miller, 1985 ), decreased hepatic sensitivity to glucagon ( Xue et al, 2000 ) and/or decreased insulin resistance through attenuation of hepatic PPARα expression ( Bernal-Mizrachi et al, 2007 ). However, ligation is non-reversible, the body may adapt to ligation over time and significant unwanted side effects may be associated with this technique such as negative changes in feeding behavior, increased hypoglycemic episodes, decreased liver regeneration and increased metastasis during liver cancer ( Okazaki et al, 1993 ; Kiba, 2002 ; Donovan and Watts, 2014 ; Hiramoto et al, 2017 ). In one study hepatic vagotomy decreased insulin levels and increased PG ( Okazaki et al, 1993 ).…”
Section: Introductionmentioning
confidence: 99%